Community Survey Report: Pokhara-Lekhnath, Ritthepani-27, Nepal - Pokharel, Durga; Shrestha, J; KC, Mamata; Thapa, M; Ranabhat, N; Dhakal, R; Poudel, R; Khadka, S; Phuyal, S; Nepali, S; Acharya, S; Poudel, S; et al. (Journal of Gandaki Medical College-Nepal, 2018)
Community diagnosis is defined as a comprehensive assessment of the state of an entire community in relation to its social, economic, physical and biological environment. It is a process of examining the patterns of disease or health status in the community in order to promote health, prevent disease and manage health services for the community people. As per the curriculum of Tribhuwan University, B.Sc. Nursing first year, we were provided an opportunity to fulfill the practicum of community health nursing in the assigned area Shanti Tole and Teentara Tole, Pokhara, Lekhnath, Ritthepani-27 from 18th June to 14th July 2017. Total population of Ritthepani was 4529, male population was 2100 and female population was 2429. Each of the 13 students was assigned with 10 different families for community diagnosis in order to promote the health of the individual, family and community.The main objective of community diagnosis was to find out the health related aspects and to provide preventive, promotive, curative and rehabilitative services to the individual and the community as a whole.All the findings were presented among the key members of the community. On survey, total population of 130 houses was found 565, among them 296 were male population and 269 were female population. Sanitation of the community was inappropriate. People were not using the health facilities effectively so they were found suffering from different kinds of diseases most commonly gastritis. The common health seeking practice was going to governmental hospital and traditional healers.